Pembangunan Energi Baru Terbarukan Sumur Ladang Berbasis Internet of Things di Kalurahan Sitimulyo - Abadi, Anis Susila; Hendriana, Yana; Taruno, Restiadi Bayu; Mardhiyyah, Rodhiyah (Universitas Muhammadiyah Yogyakarta, 2025)
Food crops, horticulture, rice, and secondary crops are grown on 12 hectares of agricultural land in the Pagergunung I and Pagergunung II Hamlets of Sitimulyo District. The primary issue that farmers deal with is the scarcity of water, particularly during the dry season. Commonly, diesel engines are used for water management because there are no electrical sources near agricultural land, resulting in the overall waterneeds not being fulfilled and may lead to the degradation of agricultural land. The goal of this community service initiative is to construct an irrigation system using submersible water pumps that are powered by Internet of Things (IoT)-based New Renewable Energy (EBT) technology. Consequently, the farmers in Pagergunung I and Pagergunung II Hamlets are able to overcome their challenges thanks to the creation of this system. An Arduino microcontroller served as the control center for the irrigation system’s design, a selenoid valve opened and closed water channels, solar panels provided electrical power, and the Ubidots application served as the system’s user interface. The activity’s outcomes demonstrate that solar panels can provide electricity when it is sunny, that irrigation management can be controlled with applications, and that the constructed irrigation system can irrigate agricultural land uniformly.